2009
DOI: 10.1038/ncb1839
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin ligase CHIP acts as an upstream regulator of oncogenic pathways

Abstract: CHIP is a U-box-type ubiquitin ligase that induces ubiquitylation and degradation of its substrates, which include several oncogenic proteins. The relationship between CHIP and tumour progression, however, has not been elucidated. Here, we show that CHIP suppresses tumour progression in human breast cancer by inhibiting oncogenic pathways. CHIP levels were negatively correlated with the malignancy of human breast tumour tissues. In a nude mouse xenograft model, tumour growth and metastasis were significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
169
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(184 citation statements)
references
References 30 publications
13
169
1
1
Order By: Relevance
“…(3) Several groups have reported that Runx2 protein stability is controlled through a ubiquitinproteasome-mediated protein degradation mechanism by Smurf1, (4) Schnurr-3 (Shn3)/WWP1, (5) and CHIP. (6) CHIP/STUB1 is a cochaperone protein identified through its interaction with Hsc/Hsp70, (7) and promotes the ubiquitination and degradation of chaperone-bound proteins, including receptor tyrosine kinase ErbB2, glucocorticoid receptor, (8) SCR-3, (9) Smads, and the mis-folded cystic fibrosis transmembrane conductance regulator protein. (10) Previously, we found that CHIP negatively regulates osteoblast differentiation by mediating degradation of Runx2.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Several groups have reported that Runx2 protein stability is controlled through a ubiquitinproteasome-mediated protein degradation mechanism by Smurf1, (4) Schnurr-3 (Shn3)/WWP1, (5) and CHIP. (6) CHIP/STUB1 is a cochaperone protein identified through its interaction with Hsc/Hsp70, (7) and promotes the ubiquitination and degradation of chaperone-bound proteins, including receptor tyrosine kinase ErbB2, glucocorticoid receptor, (8) SCR-3, (9) Smads, and the mis-folded cystic fibrosis transmembrane conductance regulator protein. (10) Previously, we found that CHIP negatively regulates osteoblast differentiation by mediating degradation of Runx2.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies demonstrate that an impairment of chaperone-assisted degradation causes diverse diseases and age-related pathologies (Zhang and Cuervo, 2008;Kajiro et al, 2009;Selcen et al, 2009). The 'degrading' activity of certain chaperones apparently fulfills an essential function within the proteostasis network.…”
Section: Introduction: Chaperone-assisted Degradation Is Essential Fomentioning
confidence: 99%
“…We previously reported that the expression levels of CHIP mRNA were lower in breast cancer tissue than in normal breast tissue. Furthermore, immunohistochemical staining indicated that the expression levels of CHIP proteins were also lower in breast cancer cells 4. However, the mechanisms underlying the down‐regulated expression of CHIP in breast cancer currently remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…CHIP has been shown to suppress the expression of other oncogenic proteins that enhance anchorage‐independent tumor growth and metastatic potential in breast tumors. Our previous findings indicated that the down‐regulated expression of CHIP led to the accumulation of SRC‐3, thereby resulting in enhanced tumor migration and invasion through increases in Smad and Twist gene transcription 4, 5. Smad and Twist have recently been shown to favor the metastatic dissemination of cancer cells through their abilities to induce epithelial–mesenchymal transition 6, 7.…”
Section: Introductionmentioning
confidence: 99%